Next generation business handbook : - Chowdhury, Subir (John Wiley, 2004)
Next Generation Business Handbook offers strategies for the next generation of business success from the best business schools around the world. Presents fresh ideas from the young, up-and-coming business thinkers and experts from the world's best business schools. Coverage of topics like career imprinting and operating in a virtual workspace that are receiving increased attention in organizations. Organized around Chowdhury's "next generation business model.